Deletion of the ecdysis-triggering hormone gene leads to lethal ecdysis deficiency. - Park, Y.; Filippov, V.; Gill, S.S.; Adams, M.E. (Development, 2002)
At the end of each developmental stage, insects perform a stereotypic behavioral sequence leading to ecdysis of the old cuticle. While ecdysis-triggering hormone (ETH) is sufficient to trigger this sequence, it has remained unclear whether it is required. We show that deletion of eth, the gene encoding ETH in Drosophila, leads to lethal behavioral and physiological deficits. Null mutants (eth(-)) fail to inflate the new respiratory system on schedule, do not perform the ecdysis behavioral sequence, and exhibit the phenotype buttoned-up, which is characterized by incomplete ecdysis and 98% mortality at the transition from first to second larval instar. Precisely timed injection of synthetic DmETH1 restores all deficits and allows normal ecdysis to occur. These findings establish obligatory roles for eth and its gene products in initiation and regulation of the ecdysis sequence. The ETH signaling system provides an opportunity for genetic analysis of a chemically coded physiological and behavioral sequence.